Social spending for inclusive growth in the Middle East and Central Asia - Mathai, Koshy; Duenwald, Christoph; Guscina, Anastasia (Washington, D.C International Monetary Fund (IMF), 2020)
This paper examines the role of social spending in improving socioeconomic outcomes in the Middle East and Central Asia. In particular, it addresses the following questions: (1) how large is social spending across the region? (2) how do countries in the region fare on socioeconomic outcomes? (3) how important is social spending as a determinant of these outcomes? and (4) how efficient is social spending in the region? (IMF page)
Acknowledgments -- Executive Summary -- 1. Introduction -- 2. Defining Social Spending -- 3. The Level of Social Spending in the Middle East and Central Asia -- 4. Socioeconomic Outcomes in the Middle East and Central Asia -- 5. Impact of Social Spending on Socioeconomic Outcomes -- 6. Increasing the Efficiency of Social Spending in the Region -- 7. Drivers of Efficiency: Institutions and Governance -- 8. Takeaways and Policy Implications
Includes bibliographical references (p.91-95)
Keywords: Debt and public expenditure; PUBLIC EXPENDITURE; SOCIAL EXPENDITURE; SOCIOECONOMIC IMPACTS; CENTRAL ASIA; MIDDLE EAST